2008
DOI: 10.1245/s10434-008-0249-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Postoperative Infection on Long-Term Survival After Potentially Curative Resection for Gastric Cancer

Abstract: We focused on the impact of postoperative infection on long-term survival after potentially curative resection for gastric cancer. Postoperative surgical and medical complications have been implicated as a negative predictor of long-term outcome in various malignancies. However, there have been no published reports assessing the impact of complications arising from postoperative infection on survival in gastric cancer. We studied a population of 1,332 patients who underwent curative resection for gastric cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
102
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 30 publications
8
102
0
1
Order By: Relevance
“…However, despite these numerous studies, only three previous studies [7][8][9] demonstrated a correlation between infectious complications and poor survival in patients with gastric cancer. However, there were some drawbacks in these studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, despite these numerous studies, only three previous studies [7][8][9] demonstrated a correlation between infectious complications and poor survival in patients with gastric cancer. However, there were some drawbacks in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies [1][2][3][4][5][6][7][8][9] have demonstrated that the development of postoperative complications increased the risk of disease recurrence in various types of malignancies. Among surgical morbidities, infectious complications are the most frequent and directly related to surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the postoperative complications were risk factors for the survival or disease recurrence in various types of malignancies 7, 8, 9, 10, 11, 12. Furthermore, some authors have shown that the immunological response against postoperative complications enhanced the viability of undetectable residual tumor cells after surgery, thereby increasing the risk of disease recurrence 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…Özellikle solunum yolları enfeksiyonları ilk sırada yer alması ve sonuçları nedeniyle üzerinde önemle durulması gereken sorunlardır (15)(16)(17). En tehlikeli komplikasyon hastaların %3-12'sinde görülen anastomoz kaçaklarıdır.…”
Section: Bulgularunclassified